Cocoa marketing in the Malimpia parish of Quinindé canton: Analysis of the macro and microenvironment (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
Cocoa marketing in Ecuador represents one of the main economic activities that generate employment. The objective was to analyze the macro and micro-environmental factors that influence cocoa marketing in the Malimpia parish of Quinindé canton. For this purpose, a descriptive and exploratory research was carried out. The information was collected through interviews and documentary review. The results showed opportunities that favor the commercialization of the bean. The analysis of the microenvironment revealed high rivalry among marketing companies, low bargaining power of suppliers, and medium bargaining power of buyers. In addition, threats from new entrants and exit barriers were identified and it was found that there are no substitutes for cocoa beans. It was concluded that among the final proposals is the participation in working groups that transcend the borders of cocoa marketing in the canton and the Malimpiay Parish and even the province, to benefit through the evaluation of management plans that are carried out in other areas and measure the possibility of replicating or contributing to producers of the same agronomic species through a research and development network to enhance the economy and strengthen the bonds of strategic alliances.